The Effect of Vibratory Grinding Time on Moisture Sorption, Particle Size Distribution, and Phenolic Bioaccessibility of Carob Powder - Červenka, Libor; Frühbauerová, Michaela; Palarčík, Jiří; Muriqi, Sali; Velichová, Helena (Molecules (Basel, Switzerland), 2022)
Carob pod powder, an excellent source of health-promoting substances, has found its use in a wide range of food products. Grinding conditions affect the physical and chemical properties of the powder, but their influence on the bioaccessibility of phenolic compounds in carob pod powder has not yet been determined. The carob pods were ground for 30-180 s in a vibratory grinder. The median values (D50) of particle size decreased after 60 s of grinding (87.9 μm), then increased to 135.1 μm. Lightness showed a negative correlation with D50 and aw, while the values of redness and yellowness decreased with the reduction in particle size and water activity. The smaller the value of D50, the higher the equilibrium moisture content of carob powder. Phenolic acids (vanillic, ferulic, cinnamic) and flavonoids (luteolin, naringenin, apigenin) were found in all samples of carob powder. The grinding time influenced their content in carob powder, with maximum values at 180 s. Similar observations were made when assessing antioxidant capacity. The in vitro digestion process only improved the bioaccessibility of catechin content in all samples. However, the bioaccessibility of the phenolic compounds and the total phenolic and flavonoid contents decreased with the increase in grinding time. Our findings revealed that the grinding of carob pods for 180 s improved the extractability of phenolics; however, their bioaccessibility was reduced. It is sufficient to ground the carob pod for 30 s, ensuring good availability of nutraceuticals and lower energy cost for grinding.
Keywords: prášky, zásypy, pudry; Powders; HPLC analysis; in vitro digestion; Flavonoids; galaktany; Phenols; flavonoid; Particle Size; phenolic; flavonoidy; rostlinné gumy; Galactans; correlation; Plant Gums; velikost částic; fenoly; Fabaceae